The marriage of endo-cavity and exo-wall complexation provides a facile strategy for supramolecular polymerization - Wang, Shilu; Wang, Yiliang; Chen, Zhenxia; Lin, Yuejian; Weng, Linhong; Han, Kang; Li, Jian; Jia, Xueshun; Li, Chunju (Chemical communications (Cambridge, England), 2015)
Butylated pillar[5]arene (1) and N , N ′-bis( n -butyl)pyromellitic diimide (2) form a 2 : 1 sandwich-type complex external to the walls of the receptor (“exo-wall” complex). The marriage of exo-wall interactions and endo-cavity inclusion provides a new strategy for the construction of supramolecular polymers from unfunctionalized neutral receptors.